TWO-EPOCH OPTIMAL DESIGN OF DISPLACEMENT MONITORING NETWORKS - Eshagh, Mehdi; Alizadeh-Khameneh, Mohammad Amin (Boletim de Ciências Geodésicas, 2015)
In the traditional method of optimal design of displacement monitoring networks a higher precision, √2 times better than the desired accuracy of displacements, is considered for the net points in such a way that the accuracy of the detected displacements meets the desired one. However, in this paper, we develop an alternative method by considering the total number of observations in two epochs without such a simple assumption and we call it two-epoch optimisation. This method is developed based on the Gauss-Helmert adjustment model and the variances of the observations are estimated instead of the weights to optimise the observation plan. This method can deliver the same results as the traditional one, but with less required observations in each epoch.